PENGARUH KOMPENSASI EKSEKUTIF, BEBAN PAJAK TANGGUHAN DAN FAKTOR LAINNYA TERHADAP PENGHINDARAN PAJAK - Putri, Christie Dwi; Yohanes (Jurnal Akuntansi Trisakti, 2025)
The aim of this research is to obtain empirical evidence of the influence of profitability, leverage, company size, capital intensity, audit committee, executive compensation and deferred tax burden on tax avoidance. This research population used 59 samples with 177 consumer cyclical and consumer non-cyclical companies listed on the Indonesia Stock Exchange during the period 2020 to 2022 which were selected using the purposive sampling method. This research uses a multiple regression analysis method using the eview analysis tool. The research results show that profitability and company size have an effect on tax avoidance, while leverage, capital intensity, audit committee, executive compensation and deferred tax expense have no effect on tax avoidance. Companies with high profit levels tend to avoid taxes to maintain optimal performance. Large companies tend to use their resources to avoid taxes by not violating tax regulations.